Modulation of fat metabolism and gut microbiota by resveratrol on high-fat diet-induced obese mice - Campbell CL; Yu R; Li F; Zhou Q; Chen D; Qi C; Yin Y; Sun J (Diabetes, Metabolic Syndrome and Obesity, 2019)
C Linda Campbell,1,2,* Renqiang Yu,3,4 Fengzhi Li,1 Qin Zhou,3 Daozhen Chen,4 Ce Qi,1,2 Yongxiang Yin,5 Jin Sun1,2,* 1State Key Laboratory of Food Science and Technology, Jiangnan University, Wuxi 214122, China; 2School of Food Science and Technology, Jiangnan University, Wuxi 214122, China; 3Department of Neonatology, The Affiliated Wuxi Maternity and Child Health Care Hospital of Nanjing Medical University, Wuxi 214002, China; 4Department of Central Lab, The Affiliated Wuxi Maternity and Child Health Care Hospital of Nanjing Medical University, Wuxi 214002, China; 5Department of Pathology, The Affiliated Wuxi Maternity and Child Health Care Hospital of Nanjing Medical University, Wuxi 214002, China *These authors contributed equally to this work Purpose: The antioxidant resveratrol (RSV) has low bioavailability and can reach the colon to access the gut microbial ecosystem. RSV administration together with high-fat diet prevented abnormal changes of intestinal microbiota. However, whether or not RSV can reshape the intestinal microbiota of obese mice and alleviate obesity-related diseases remains to be studied. This study aimed to explore the role of RSV in alleviating high-fat-induced obesity and its relationship with oxidative stress and gut microbiota.Methods: Male C57BL/6 mice were divided into five groups and administered for 16 weeks with: standard diet (CON), high-fat diet (60% energy for lard, HFD), and HFD with low, medium, and high dose of RSV, 50, 75, and 100 mg/kg body weight administered daily via drinking water, respectively.Results: Medium and high RSV treatment significantly prevented body weight gain, decreased relative weight of liver and adipose tissue compared with HFD (P<0.05). All doses significantly prevented HFD-induced increase of serum triglyceride, low density lipoprotein cholesterol, glucose, and endotoxemia (P<0.05). Medium and high dose also prevented chronic inflammation by decreasing serum interleukin-1 and tumor necrosis factor-alpha (P<0.05), and oxidative stress in liver and brain indicated by increase in superoxide dismutase, catalase, glutathione peroxidase activity (P<0.05). Formation of malondialdehyde was prevented by all doses compared with HFD (P<0.05). Both medium and high doses of RES increased alpha diversity of gut microbiota according to the Chao1 and Shannon indices (P<0.05). Medium dose induced obvious shift in gut microbiota composition according to principal component analysis. High dose of RSV effectively prevented HFD-induced increase of Coriobacteriaceae and Desulfovibrionaceae (P<0.05), which show a significant correlation with body weight (r>0.8 P<0.00).Conclusion: RSV prevented HFD-induced endotoxemia, oxidative stress, and gut microbiota change. Keywords: resveratrol, high fat diet, obesity, oxidative stress, gut microbiota